PERTUMBUHAN DAN KELULUSHIDUPAN LARVA IKAN SIBAN (CYCLOCHEILICHTHYS APOGON) DENGAN RANGSANGAN SGNRH + DOMPERIDON DOSIS BERBEDA - Nuraini Nuraini; Syafruddin Nasution (Berkala Perikanan Terubuk, 2017)
This research was conducted in April - June 2016, which aims to determine the effect of the injection of different doses sGnRH + Domperidone on the quality and quantity of eggs, as well as the survival of fish larvae siban (Cyclocheilichthys apogon) aged 40 days. The method used in this research was the experiment method, where data were analyzed by using Anova and descriptive. The results showed that the best quality and quantity of eggs were obtained on injecting sGnRH + Domperidone with high dose of 0.7 ml / kg body weight, as well as the absolute length growth, the absolute weight growth, daily weight growth rate and survival of larvae aged 40 days also found in the treatment sGnRH + Domperidone injection of the same dose. Water quality during the study was in the range of tolerance of fish life.